The Role of Training Programs in Enhancing the Digital Skills of Records Managers in Omani Aviation Institutions - Elsawy, Elsayed; Saadi, Hamad Al; Attia, Sarah (Journal of Posthumanism, 2025)
Records managers play a vital role in information governance and records management, as they are responsible for preserving, organizing, and making records available. They also contribute to protecting sensitive data and preserving it from damage or loss. Through their important role, records managers help facilitate the decision-making process and search for the necessary information to achieve the goals and support the development of institutions. This study aimed to identify the current state of digital skills among records managers in the Omani civil aviation sector and the role of training programs in enhancing their expertise in records and information management. The study employed a qualitative approach, conducting semi-structured interviews with heads of records departments and sections in Omani aviation institutions to understand their current digital skills and the role of the training programs offered to them in enhancing these skills. The institutions included in the study are Oman Air, Oman Air Catering, Muscat Duty Free, Oman SATS Cargo, Ground Handling Services (Transom), the Civil Aviation Authority, and Oman Airports. The results revealed that institutions in the Omani civil aviation sector have not allocated sufficient training programs regarding digital records management and the use of modern technologies in records management. Specifically, 2 out of 7 institutions included in the study, or 28.6% did not provide any training programs for their employees in digital records management over the past few years. Key challenges to enhancing the digital skills of records managers include insufficient training programs, weak financial support for digital transformation, and the cost of electronic records management systems. To improve the digital skills of records managers, the study recommends providing and intensifying training programs in information technology for digital records management, such as AI applications and data analysis. It also recommends developing policies and procedures for digital records management, providing financial support for digital transformation, exchanging experiences and practices among institutions, and encouraging sharing professional knowledge among records managers in Omani civil aviation institutions.